The Combination of Hip Abductor Strengthening and Quadriceps Strengthening Exercise is Effective in Reducing Pain and Muscle Stiffness in Grade 3 Genu Dextra Osteoarthritis - Asmarasikha, Aldila Lutfi; Santoso, Totok Budi; Kingkinnarti, Kingkinnarti (Jurnal Penelitian Kesehatan SUARA FORIKES, 2026)
Knee osteoarthritis is a degenerative joint disease that commonly causes pain, stiffness, and decreased functional capacity, particularly in older adults. This study aims to evaluate the effect of physiotherapy interventions in the form of Hip Abductor Strengthening Exercise and Quadriceps Strengthening Exercise on reducing pain and muscle stiffness in patients with grade 3 right knee osteoarthritis. A case report design was used involving a 57-year-old male patient who underwent a physiotherapy program consisting of three treatment sessions, with an exercise dosage of 10 repetitions in 2 sets and a holding time of 5 seconds for each repetition. Pain intensity was assessed using the Numeric Rating Scale (NRS), while muscle stiffness was evaluated through measurements of joint range of motion (ROM) to assess joint mobility and Manual Muscle Testing (MMT) to assess muscle strength. The results demonstrated a reduction in pain intensity from NRS 5 to 3, accompanied by an increase in knee flexion range of motion from 80° to 100° and an improvement in muscle strength from MMT grade 2+ to grade 4. These findings indicate a reduction in muscle stiffness and an improvement in the patient’s motor function. In conclusion, the combination of Hip Abductor Strengthening Exercise and Quadriceps Strengthening Exercise is effective in reducing pain and muscle stiffness and in improving knee joint function in patients with grade 3 right knee osteoarthritis.Keywords: knee osteoarthritis; hip abductor strengthening exercise; quadriceps strengthening exercise; pain; muscle stiffness; physiotherapy